Transformational Leadership and Organizational Performance: The Mediating Role of Organizational Innovation - Sadia Arif; Aman Akram (SEISENSE Journal of Management, 2018)
The study is an investigation of transformational leadership impact on organizational performance; the mediating role of organizational innovation. The study revealed that organizational innovation has mediated significant impact on organizational performance. The research found that transformational leadership and organizational performance has strong relationship. Therefore, it will help the managers to create such leadership style in the organizations. Pakistani organizations need an environment where leaders motivate and encourage the employees who are wishing to become more creative and effective in leading the successful organizations.